A low ripple voltage multiplier for X-ray power supply - Iqbal, Shahid; Besar, Rosli; Venkataseshiah, C. (2008)
In this paper, a low ripple voltage multiplier (VM) for X-ray power supply is proposed. It consists of three single-phase symmetrical voltage multipliers, which are connected in series at their smoothing columns like string of batteries and are driven by three-phase ac power source. The smoothing column of each voltage multiplier is charged twice every cycle independently by respective oscillating columns and discharged in series through the load. The charging and discharging process occurs six times a cycle and the frequency of the output voltage ripple is six times the drive signal frequency. The proposed VM has three times larger output voltage and three times smaller ripple factor as compared to single-phase symmetrical VM. The simulation and experimental results of the scaled-down laboratory prototype are provided to show the feasibility of proposed VM.